Internet of Vehicles. Technologies and Services Toward Smart Cities : 6th International Conference, IOV 2019, Kaohsiung, Taiwan, November 18–21, 2019, Proceedings /: 6th International Conference, IOV 2019, Kaohsiung, Taiwan, November 18–21, 2019, Proceedings. (2020) - Unknown
No abstract available